PENGARUH SERBUK DAUN SERAI (Cymbopogon nardus L.) SEBAGAI INSEKTISIDA ALAMI DALAM MENGUSIR HAMA KUTU BERAS (Tribolium castaneum L.) - Willa; Yarsa Erianti; Syamsurizal (Jurnal Sapta Agrica, 2025)
Rice weevil (Tribolium castaneum L.) infestation poses a serious threat that directly impacts food security and the economic welfare of farmers. Pest control is often carried out using conventional synthetic pesticides. However, the use of chemical pesticides causes various problems, such as environmental pollution and health risks to humans. Therefore, this study aims to evaluate the effect of different concentrations of natural extract from citronella (Cymbopogon nardus L.) leaves on the mortality rate of rice weevils as a more environmentally friendly pest control alternative. This research was conducted using an experimental method with a completely randomized design (CRD). Several concentrations of citronella leaf powder were tested on the population of Tribolium castaneum L., with treatments of 2 grams, 4 grams, and 6 grams, along with a control group without treatment. Data collection was performed using a structured observation checklist to record the number of rice weevil mortalities in each treatment. This technique allowed the researchers to systematically observe and measure the pest’s response to the treatments. The results showed that the application of citronella leaf powder at various concentrations did not have a significant effect on rice weevil mortality. Thus, it can be concluded that citronella leaf powder as a natural insecticide was not effective in controlling rice weevil infestations under the conditions of this study. Further research is needed to identify more effective dosages or application methods to utilize the potential of citronella as an alternative natural pesticide.